PENGEMBANGAN BAHAN AJAR BOLA VOLI UNTUK SEKOLAH MENENGAH ATAS - Indah Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
Penjasorkes learning at High School emphasizes the basic movements variations into games and sports, and therefore physical education sangant expect factor of the student and the student’s learning external factors, it can not be separated from the role of an educator. This research aims to develop teaching materials volleyball materials for high school students. The approach in this study classified into research and development that will produce learning. Subjects in this stusy is a class XI student of State Senior High School 16 Banda Aceh of 20 people. The process of developing a measuring tool of teaching materials volleyball include (1) observation, (2) Consulting experts, (3) the design of the product, (4) validation of the design the product, (5) design revisions, (6) simulations products, (7) the revised products, (8) the trial use of the product, (9) the result of the product. From the research result are the calculated by using SPSS. The result of the studies that have been obtained on the basis of analysis and discussion, it can concluded that instrument teaching materials volleyball for high school students consisting of 13 items of questions of teaching materials that are valid and reliable to have a level of authenticity is high with the points index score validity 0.851 and has a level of reability that are the points tally reliability index score of 0.685. Development of teaching materials so that the product can be used as teaching materials in the learning materials volleyball for High School. Keywords: Development, Instructional Materials, Games, Volleyball